Practising Law in a Commercial Environment: Is the Customer Always Right? - O'Brien, Anne (Victoria University of Wellington Law Review, 1998)
It is maintained by some that the concept of professionalism is outdated and incompatible with the business entities which law firms have become. In this article the author examines the concept of professionalism and· the tensions that exist in modern legal practise. She concludes that, while adjustment is necessary, the two are not incompatible. Indeed continued adherence to the principle of professionalism is necessary to the health of any legal practise.